Routine phasing of coiled-coil protein crystal structures with AMPLE. (2015) - Thomas, Jens M. H.; Keegan, Ronan M.; Bibby, Jaclyn; Winn, Martyn D.; Mayansa, Olga; Rigden, Daniel J.
No abstract available